Effect of the Addition of a Buffer Gas during Pulsed Plasma-Chemical Synthesis on the Structural and Morphological Characteristics of CuxOy@SiO2 and CuxOy@TiO2 Nanocomposites; Journal of Materials Engineering and Performance; Vol. 31, iss. XX - Kholodnaya G. E. Galina Evgenievna; Ponomarev D. V. Denis Vladimirovich; Sazonov R. V. Roman Vladimirovich; Lapteva O. P. Olga Pavlovna (2022, 2022)
Title screen